Hubungan Komunikasi Terapeutik Perawat Dengan Ansietas pada Pasien Preoperasi Laparatomi di Ruang Raudhah Rumah Sakit Umum Daerah dr Zainoel Abidin Banda Aceh Tahun 2017 - ., Junardi (Jurnal Kesehatan Ilmiah Aufa Royhan, 2017)
Patients who will undergo laparatomy surgery will usually experience fear and anxiety. The anxiety that patients experience varies - the reasons for which are anxious to face the operating room, and anxious when surgery fails. Some nurses do not provide the latest information about the patient's condition. Therapeutic communication provides understanding between nurses and patients with the aim of helping patients clarify and reduce the burden of the mind and is expected to eliminate patient anxiety. The purpose of this study to determine the relationship of therapeutic nurse communication with anxiety in laparatomi preoperative patients in space Raudhah Regional General Hospital dr. Zainoel Abidin Banda Aceh. This research is analytic with cross sectional approach. Sampling of this research using purposive sampling technique amounted to 61 patients in space Raudhah. This research was conducted on 3 July - 3 September 2017 by distributing questionnaires. Data analysis is done using computer software. The results showed therapeutic nurse communication both 60 0rang (98.4%) and anxiety in light patients 27 people (44.3%). The result of chi-square statistic test shows that there is a therapeutic communication relationship of nurse with anxiety in laparatomy preoperative patient at Dr Zainoel Abidin Banda Aceh General Hospital (p-value = 0.000). It is expected to increase for the nurse in conducting therapeutic communication to patient especially in preoperative preparation so that patients do not experience anxiety